Ministerial decree 5/2017 concerning the rules for importing drugs raw materials biologicals formula milk and medical supplies from reference and non reference countries = قرار وزاري رقم 5 لسنة 2017 بشأن قواعد استيراد الأدوية والخامات والمستحضرات الحيوية وألبان الأطفال والمستلزمات الطبية من الدول المرجعية وغير المرجعية - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
Ministry of health and population decree no. 5 of the year 2017 concerning the rules for importing drugs, raw materials, biologicals, formula milk and medical supplies from reference and non-Reference countries وزاارة الصحة والسكان قرار رقم 5 لسنة 2017 بشأن قواعد استيراد الأدوية والخامات والمستحضرات الحيوية وألبان الأطفال والمستلزمات الطبية من الدول المرجعية وغير المرجعية